MOTIVATIONAL LEADERSHIP STRATEGY IN SDN 3 KAWO, PUJUT SUBDISTRICT, CENTRAL LOMBOK - Agus Argawan Budi (Institut Pemerintahan Dalam Negeri, 2021)
This article discusses motivational leadership that is critical to organizational development and progress. Leaders who have a charismatic attitude, are able to provide inspiration, provide motivation and attention to team members, and stimulate all components to make changes in order to achieve organizational goals. The research method used is literature review method with descriptive research type. Research results: strategies to play a motivational leadership role in SDN 3 Kawo can be done by scheduling activities to provide motivation to students and taking a behavioral approach to teachers and/or employees at any time and opportunity. In conclusion that the quality of public service is highly determined by the quality of leadership knowledge, a leader must learn and understand the concepts of leadership, motivation and behavior that can be a reference material for the study and research of leadership behavior, as well as the development of the ideal motivational leadership paradigm.